A hybrid control strategy for Z-source inverter DG systems - Girgin, Ozgun; Sarul, Mustafa Hadi (KOREMA, 2019)
A hybrid control system for Z-source inverter (ZSI) with LC filter which is used in distributed generation (DG) systems is presented in this study. The proposed system has two different controllers, dc-side and ac-side. While designing the ac-side controller, a proportional-resonant (PR) controller was used. Besides, to be a ble to adjust the voltage of the Z-source capacitor according to the reference value of it, a proportional-integral (PI) controller was employed on the dc-side of the ZSI. In the end, a dynamic ZSI model was obtained by the help of small signal analysis and state space averaging. After the mathematical model of the ZSI was derived, the dc-side and ac-side controllers were designed. Using both controllers, inverter reference tracking performance was enhanced. The proposed controller offers superior output voltage regulation regardless of the linear and nonlinear loads. Taking into account the abrupt variations in both the dc source and linear/nonlinear load level, the effectiveness of the proposed control system was tested and supported by Matlab (R)/Simulink simulations.
Keywords: dc-ac power converters; distributed generation systems; inverters; power system dynamics; proportional plus resonant controller; VOLTAGE; DESIGN; MODEL; Automation & Control Systems; Engineering